Implementation Of The Lecture Plus Question And Answer Method In Enhancing Students' Learning Motivation At Tadika Suriah Edukids Centre, Malaysia - Isman Efendi Limbong; Nadya Dwi Haryuni (Yayasan Rahmat Islamiyah, 2026)
This study aims to describe the implementation of the lecture method combined with the question-and-answer technique (ceramah plus tanya jawab) in enhancing the learning motivation of preschool children at Tadika Suriah EduKids Centre, Malaysia. A qualitative descriptive case study design was employed, involving the class teacher and preschool children aged four to six years as research subjects. Data were collected through classroom observation, semi-structured interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing, with source and technique triangulation applied to ensure trustworthiness. The findings indicate that the combined method was implemented in three stages: lesson preparation, delivery of material through communicative and expressive lecturing, and a guided question-and-answer session. The integration of guided questioning into the lecture sessions was found to stimulate children's attention, participation, and willingness to respond, indicators commonly associated with increased intrinsic and extrinsic learning motivation. Supporting factors included the teacher's communication skills, the use of simple instructional media, and a conducive classroom climate, while inhibiting factors included limited session time and variation in children's language development. The study concludes that the lecture-plus-question-and-answer method is a practical and developmentally appropriate strategy for strengthening young children's motivation to learn in a preschool setting.